Construct validity of data from a TPACK self-assessment instrument in 2-year public college faculty in the United States. Issue 4 (6th August 2020) - Scott, Kristin C.; Nimon, Kim
Abstract: Mishra and Koehler's technological pedagogical content knowledge (TPACK) theory can help provide the framework for measuring needed knowledge, skills, and abilities (KSAs) in faculty members at 2-year public colleges. This study tests a self-assessment survey in a large sample of 2-year public college faculty members. Using factor analysis, the Community College TPACK Survey for Meaningful Learning (CC-TSML) is found to demonstrate internal reliability, adequate model fit, and composite reliability. Use of this instrument can help faculty members and administrators determine what type of interventions may be necessary to help faculty achieve the needed KSAs as measured by the CC-TSML, including professional development.